2019
DOI: 10.1136/bmjopen-2019-030646
|View full text |Cite
|
Sign up to set email alerts
|

Rates of retention of persons with a mental health disorder in outpatient smoking cessation and reduction trials, and associated factors: protocol for a systematic review and meta-analysis

Abstract: IntroductionSmoking among persons with a mental health disorder is associated with inequitable health, social and economic burden. Randomised controlled trials (RCTs) are considered the gold standard design for the assessment of healthcare intervention efficacy/effectiveness. However, many RCTs of smoking interventions for persons with a mental health disorder lack rigour due to low participant retention. No systematic review has pooled retention rates in randomised trials of smoking interventions for persons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Although it is not possible to make a direct comparison on trial design/population with the STEPS paper, it is interesting that over 10 years later, recruitment still remains a significant barrier in successful trial completion. Similarly, in line with previous studies, we also found evidence of poor retention rates in trials of psychological interventions [ 15 ]. Only 47% of the studies achieved their specified follow-up rate even with extensions, indicating that the majority of trials were potentially under-powered.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although it is not possible to make a direct comparison on trial design/population with the STEPS paper, it is interesting that over 10 years later, recruitment still remains a significant barrier in successful trial completion. Similarly, in line with previous studies, we also found evidence of poor retention rates in trials of psychological interventions [ 15 ]. Only 47% of the studies achieved their specified follow-up rate even with extensions, indicating that the majority of trials were potentially under-powered.…”
Section: Discussionsupporting
confidence: 92%
“…Whilst average retention in trials has been estimated at 89% [13], which may suggest that retention is less of a concern than recruitment, this figure is likely inflated by trials with only short-term follow-ups. Retention has also been shown to be particularly challenging in certain clinical groups or types of intervention, such as behavioural intervention trials involving participants with a mental health disorder [15]. Studies on smoking cessation for participants with depression or substance use disorders, for example, have reported follow-up rates as low as 27-33% [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 2 main predictors of dropout: having a smoking partner at baseline and lower mental health scores as indicated by the Depression Anxiety Stress Scale [ 50 ]. Both predictors are known to be associated with poorer treatment outcomes [ 51 ]. This finding suggests that neither of the interventions used in this study sufficiently reduced the barriers to successful intervention completion.…”
Section: Discussionmentioning
confidence: 99%